2012
DOI: 10.3945/ajcn.111.022954
|View full text |Cite
|
Sign up to set email alerts
|

Increased intake of oily fish in pregnancy: effects on neonatal immune responses and on clinical outcomes in infants at 6 mo

Abstract: Oily fish intervention in pregnancy modifies neonatal immune responses but may not affect markers of infant atopy assessed at 6 mo of age. This trial is registered at clinicaltrials.gov as NCT00801502.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
117
0
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(124 citation statements)
references
References 43 publications
2
117
0
5
Order By: Relevance
“…) Both lean and oily fish decreased plasma TAG Miles et al, 2011;Urwin et al, 2012Urwin et al, , 2014Noakes et al, 2012 Investigation of the impact of salmon in pregnancy; diet ingredients for the farmed salmon were specifically selected to be low in contaminants ( The salmon diet increased EPA and DHA in plasma PC in maternal blood, umbilical cord blood and breast milk, and decreased secretory IgA in breast milk (immunological factor provided in the milk). Maternal salmon consumption did not affect maternal or infant fecal microbiota or infant fecal IgA.…”
Section: Moore Et Al 2006mentioning
confidence: 99%
“…) Both lean and oily fish decreased plasma TAG Miles et al, 2011;Urwin et al, 2012Urwin et al, , 2014Noakes et al, 2012 Investigation of the impact of salmon in pregnancy; diet ingredients for the farmed salmon were specifically selected to be low in contaminants ( The salmon diet increased EPA and DHA in plasma PC in maternal blood, umbilical cord blood and breast milk, and decreased secretory IgA in breast milk (immunological factor provided in the milk). Maternal salmon consumption did not affect maternal or infant fecal microbiota or infant fecal IgA.…”
Section: Moore Et Al 2006mentioning
confidence: 99%
“…A number of clinical trials of fish oil intervention during pregnancy have reported modulation of the neonatal immune response towards a less allergenic phenotype and lower rates of eczema and sensitization in the first year of life [80,[82][83][84]. The similarity between the cohort studies and the individual nutrient RCTs highlights the possibility that alterations in fatty acids in the food supply may be an important factor in reducing the rates of allergic disease.…”
Section: Balance Of N-3 and N-6 Long Chain Polyunsaturated Fatty Acidsmentioning
confidence: 98%
“…There is some evidence that increased intake of EPA and DHA during human pregnancy has an effect on the immune system of the baby (163)(164)(165) and that this is linked to reduced allergic symptoms later in childhood (163,166,167) . Best et al (168) reported a meta-analysis of offspring clinical outcomes from trials of increased maternal intake of very long chain n-3 fatty acids in pregnancy.…”
Section: Inflammationmentioning
confidence: 99%